Epidemiology and outcomes of marked elevations of alanine aminotransferase >1000 IU/L in an Australian cohort. Issue 2 (18th July 2019) - Con, Danny; Buckle, Andrew; Nicoll, Amanda J; Lubel, John S
Abstract : Background and Aim: Marked elevations of alanine aminotransferase (ALT) are caused by a limited number of underlying pathologies, including hepatic ischemia, drugs/toxins, viral hepatitis, and—rarely—autoimmune hepatitis. The aim of this study was to determine the relative incidence of pathologies resulting in ALT greater than 1000 IU/L and factors predicting clinical outcomes in an Australian cohort. Methods: A retrospective cohort study of all adult patients with ALT levels greater than 1000 IU/L between January 2013 and December 2015 was conducted at a large teaching hospital network in Australia. Multivariable logistic regression analysis was used to determine predictors of etiology and mortality. Results: There were 287 patients identified with ALT levels greater than 1000 IU/L. The most common causes were ischemia (44%), drugs/toxins (19%), biliary obstruction (16%), and viral hepatitis (7%). Independent predictors of a diagnosis of ischemic hepatitis included (adjusted odds ratio; 95% confidence interval): hypotension (29.2; 8.2–104.7), chronic obstructive pulmonary disease (COPD) (20.2; 2.8–145.3), coronary artery disease (12.9; 1.7–98.9), congestive cardiac failure (7.8; 1.2–49.2), diabetes mellitus (7.4; 1.6–33.9), metabolic acidosis (6.2; 2.0–19.4), gamma‐glutamyltransferase < 135 IU/L (5.1; 1.5–17.6), and albumin <34 g/L (3.4; 1.1–11.0). Independent risk factors for all‐cause 28‐day mortality included: septic shock (14.7; 4.3–50.7), metabolic acidosis (7.3; 2.5–21.3), history of COPD (5.4; 1.6–17.8), cardiogenic shock (4.3; 1.6–11.7), prothrombin time ≥ 20 s (3.7; 1.5–9.2), and age ≥ 65 years (3.0; 1.3–7.2). Conclusions: Ischemic hepatitis was the most common cause of ALT levels greater than 1000 IU/L and was associated with high mortality. Abstract : Common causes of marked alanine aminotransferase derangement include liver ischemia, drugs/toxins, biliary obstruction, and viral hepatitis. Determination of etiology and outcomes of patients with severe liver injury can be guided by clinical and biochemical parameters.